Bone density, fractures and the associated factors in iranian children and adolescent with Osteogenesis Imperfecta - Pooran Mohsenzade; Anis Amirhakimi; Naser Honar; Forough Saki; Gholam Hossein Ranjbar Omrani; Mohammadhosein Dabbaghmanesh (BMC, 2021)
Abstract Backround Osteogenesis imperfecta(OI) is a frequent bone fragility disorder in children. The purpose of this study was to assess the BMD and Vitamin D level in children with OI in southern Iran. Method This case-control study was conducted on 23 children, clinically diagnosed as osteogenesis imperfecta and 23 age- and gender-matched healthy controls. Demographic and anthropometric data, biochemical parameters, puberty, sun exposure and physical activity were assessed. Bone mineral density (BMD) was measured by Dual-energy X-ray absorptiometry (DXA). Data analysis was done by SPSS22. Results Forty-three point four percent of OI patients and fifty-six point five percent of control group had vitamin D deficiency (P = 0.376). Thirteen OI patients (56%) had low bone mass for chronological age in lumbar area (P < 0.001). Fracture episodes during treatment was significantly influenced by time of Pamidronate start, courses of Pamidronate injection, puberty and sun exposure (P values = 0.015, 0.030, 0.044 and 0.032, respectively). Fracture episodes during treatment had significantly increased in patients who had received Pamidronate more than 3 years compared with those received less than 3 years(P values = 0.047). Conclusions This study showed that vitamin D deficiency is prevalent amongst OI children in southern Iran. More than half of the OI children had low bone mass for chronological age in lumbar area, despite receiving bisphosphonate therapy. The present results revealed that early initiation of Pamidronate and number of Pamidronate courses are associated with lower fracture rate. However, treatment period more than 3 years can have adverse effect on fracture rates.